Investigation of the multiaxial fatigue behaviour of 316 stainless steel based on critical plane method. - Sánchez-Cruces, Manuel Alejandro; López-Crespo, Pablo; Bressan, Stefano; Itoh, Takamoto (Wiley, 2019)
In this work the multiaxial behaviour of 316 stainless steel is studied under the lens of critical plane approach. A series of experiments were developed on dog bone shaped hollow cylindrical specimens made of type 316 stainless steel. Five different loading conditions were assessed with: (i) only tensile axial stress, (ii) only hoop stress, (iii) combination of axial and hoop stresses with square shape, (iv) combination of tensile axial and hoop stresses with Lshape and (v) combination of compressive axial and hoop stresses with L-shape. The fatigue analysis is performed with four different critical plane theories, namely Wang-Brown, FatemiSocie, Liu I and Liu II. The efficiency of all four theories is studied in terms of the accuracy of their life predictions and crack failure plane angle. The best fatigue life predictions were obtained with Liu II model and the best predictions of the failure plane were obtained with Liu I model.
https://v2.sherpa.ac.uk/id/publication/6807?template=romeo
Keywords: Acero inoxidable; Materiales - Fatiga; Deformaciones (Mecánica); 316 stainless steel; Biaxial fatigue; Critical plane method; Multiaxial fatigue; Nonproportional loading; Ratchetting